2014
DOI: 10.1017/s0007114514002074
|View full text |Cite
|
Sign up to set email alerts
|

Do patients living with ulcerative colitis adhere to healthy eating guidelines? A cross-sectional study

Abstract: Ulcerative colitis (UC) is an inflammatory bowel disease that causes gastrointestinal lesions, bleeding, diarrhoea and nutritional complications. Insufficient nutrient intake can additionally deteriorate nutritional status. The present cross-sectional study aimed to determine whether UC patients adhere to national dietary guidelines and to assess their dietary habits. An online questionnaire (n 93) was used to assess health-related conditions, current nutritional knowledge, professional dietary guidance and fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 26 publications
2
27
1
1
Order By: Relevance
“…Up to 71% of patients with IBD believe diet affects their disease symptoms, with 90% of CD patients and 71% of UC patients employing elimination diets while in remission [14,15]. Dietary modification can be of concern if patients drastically reduce or completely avoid nutritionally important foods/food groups, as this may place them at increased risk for developing nutritional deficiencies [16], as well as poorer quality of life. Up to 77.1% of patients with IBD report avoidance of particular foods [14].…”
Section: Introductionmentioning
confidence: 99%
“…Up to 71% of patients with IBD believe diet affects their disease symptoms, with 90% of CD patients and 71% of UC patients employing elimination diets while in remission [14,15]. Dietary modification can be of concern if patients drastically reduce or completely avoid nutritionally important foods/food groups, as this may place them at increased risk for developing nutritional deficiencies [16], as well as poorer quality of life. Up to 77.1% of patients with IBD report avoidance of particular foods [14].…”
Section: Introductionmentioning
confidence: 99%
“…These findings are supported in a UK survey of patients with ulcerative colitis, in which adherence to national dietary guidelines was poor and food avoidance strategies led to nutritional inadequacy. 4 The risk of nutritional imbalance should encourage clin icians to monitor dietary intake of their patients with IBD and help guide them through the labyrinth of ideas and concepts to which they are being exposed. Besides the use of exclusive enteral nutrition (EEN), most 'best-evidence' guidelines offer no recommendations for the use of diet in IBD.…”
Section: Introductionmentioning
confidence: 99%
“…Introduction : Recent studies have shown that food avoidance in people with inflammatory bowel disease (IBD) is far more common than in the general population, and adherence to dietary guidelines is poor. These factors may contribute to both under‐ and over‐nutrition . Furthermore, studies report that limited dietary guidance is provided to this population .…”
Section: Exploring Food Avoidance Behaviors In Outpatients With Inflamentioning
confidence: 99%